Qāṭl al-Khaṭa’: The Contextual Relevance of QS. An-Nisā’ Verse 92 to Traffic Accidents Caused by Human Error - Adinda Mawaddatul Urfah; Masruhan; Indah Khoirun Nisa’ (Jurnal test, 2026)
QS. An-Nisā’:92 emphasizes the responsibility of perpetrators of qatl al-khaṭa’ (unintentional killing) through the obligation to free a Muslim slave, pay diyat, or fast as kaffārat. This verse not only contains legal provisions, but also offers a moral framework and restorative justice that is relevant to cases of traffic accidents caused by negligence. This study aims to examine the classification of traffic accidents due to negligence as qatl al-khaṭa' in the perspective of Islamic law and compare it with Indonesian positive law regulations. The research uses a qualitative approach with library research and Hans-Georg Gadamer's hermeneutic analysis methods, through the stages of pre-understanding, dialogue with the text, and fusion of horizons to link the meaning of QS. An-Nisā':92 with contemporary legal reality. The results of the study show that traffic accidents caused by negligence fall under the category of qatl al-khaṭa’, which carries moral, legal, and social consequences that require the perpetrator to be held proportionally accountable. In Indonesian positive law, the handling of similar cases focuses on criminal sanctions, while compensation for victims and/or heirs is partly facilitated through the Jasa Raharja social insurance compensation scheme as basic state protection, not diyat imposed directly on the perpetrator. This pattern provides material compensation, but does not fully accommodate relational and spiritual recovery as outlined in QS. An-Nisā':92, so that the principle of justice in this verse can be used as an ethical reference to enrich the design of traffic accident settlements in Indonesia.